2019
DOI: 10.1371/journal.pone.0224486
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of smoking on cardiac or non-cardiac death according to age

Abstract: Tobacco smoking causes cardiovascular diseases, lung disease, and various cancers. Understanding the population-based characteristics associated with smoking and the cause of death is important to improve survival. This study sought to evaluate the differential impact of smoking on cardiac or non-cardiac death according to age. Data from 514,866 healthy adults who underwent national health screening in South Korea were analyzed. The participants were divided into three groups: never-smoker, ex-smoker or curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…For this reason, our study further extends knowledge in the field by strictly defining the SMuRF based on medical records and laboratory values during hospitalization. Moreover, only never smokers were included as nonsmokers, as compared to previous analyses where ex-smokers were considered nonsmokers due to the persistent negative impact of smoking on cardiovascular mortalities even after cessation ( 7 9 , 44 46 ). Interestingly, although the proportions of SMuRF-less were 25% ( 8 ), 19% ( 7 ), and 15% ( 9 ) for STEMI patients in the previous studies, our study revealed <6% for STEMI and NSTEMI patients without SMuRF, which may, in part, be explained by the detection of SMuRF in our study.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, our study further extends knowledge in the field by strictly defining the SMuRF based on medical records and laboratory values during hospitalization. Moreover, only never smokers were included as nonsmokers, as compared to previous analyses where ex-smokers were considered nonsmokers due to the persistent negative impact of smoking on cardiovascular mortalities even after cessation ( 7 9 , 44 46 ). Interestingly, although the proportions of SMuRF-less were 25% ( 8 ), 19% ( 7 ), and 15% ( 9 ) for STEMI patients in the previous studies, our study revealed <6% for STEMI and NSTEMI patients without SMuRF, which may, in part, be explained by the detection of SMuRF in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Study patients were categorized by smoking status and changes before and after AF diagnosis ( Figure 1 ). Smoking status was evaluated using a self-reported questionnaire in the first and second health examinations [ 19 , 20 , 21 , 22 , 23 , 24 ]. In this self-reported questionnaire, subjects chose one answer among “never smokers,” “ex-smokers”, and “current smokers” and recorded the cumulative amount of their smoking as packs per year.…”
Section: Methodsmentioning
confidence: 99%
“…[27,28] Nonetheless, our observation on the stronger association of cigarette smoking with non-cardiovascular than cardiovascular mortality is in keeping with the results of previous studies in the elderly. [29][30][31] There is indeed a strong association between cigarette smoking and non-cardiovascular disease such as cancers and chronic respiratory diseases. [32] In China, 27.8%, 18.2% and 19.6% of the deaths that are attributable to smoking are cancers, respiratory diseases and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%